1996
DOI: 10.1002/(sici)1097-0320(19961215)26:4<286::aid-cyto8>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric HLA-B27 typing using CD3 gating and molecules of equivalent soluble fluorochrome (MESF) quantitation

Abstract: The determination of HLA‐B27 (B27) status is important in the diagnosis of ankylosing spondylitis, Reiter's disease, and other arthropathies. Flow cytometric (FCM) typing of B27 is a relatively new method which allows for rapid turnaround time and low cost. However, different leukocyte populations may manifest significant variation in staining intensity with B27 antibodies. Therefore, gating utilizing only light scatter properties of cells may lead to high readings in some B27‐negative samples. Fluorescence ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In conclusion, our 3.5‐year experience with HLA‐B27 EQA scheme has shown that flow cytometry can identify HLA‐B27 pos samples (i.e., the subtype HLA‐B*2705, prevalent in the caucasoid population), but that cross‐reactivity of the commonly used HLA‐B27 MoAb is a major problem that frequently leads to false‐positive test results. HLA‐B27 typing by flow cytometry may be further improved by (i) application of quantitative flow cytometry to standardize the distinction between relatively dim (cross‐reactive) and strong (true positive) signals (32, 33); (ii) complete documentation of the reactivity of all currently defined HLA‐B27 alleles (i.e., B*2701 to B*2715) with the available anti‐HLA‐B27 MoAb; and (iii) rigorous analysis of the cross‐reactivity patterns of these MoAb with HLA‐antigens other than HLA‐B27. We feel that there will remain a place for cost‐effective and simple screening methods for selected HLA alleles, such as HLA‐B27, in the clinical diagnostic laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our 3.5‐year experience with HLA‐B27 EQA scheme has shown that flow cytometry can identify HLA‐B27 pos samples (i.e., the subtype HLA‐B*2705, prevalent in the caucasoid population), but that cross‐reactivity of the commonly used HLA‐B27 MoAb is a major problem that frequently leads to false‐positive test results. HLA‐B27 typing by flow cytometry may be further improved by (i) application of quantitative flow cytometry to standardize the distinction between relatively dim (cross‐reactive) and strong (true positive) signals (32, 33); (ii) complete documentation of the reactivity of all currently defined HLA‐B27 alleles (i.e., B*2701 to B*2715) with the available anti‐HLA‐B27 MoAb; and (iii) rigorous analysis of the cross‐reactivity patterns of these MoAb with HLA‐antigens other than HLA‐B27. We feel that there will remain a place for cost‐effective and simple screening methods for selected HLA alleles, such as HLA‐B27, in the clinical diagnostic laboratory.…”
Section: Discussionmentioning
confidence: 99%